3D Kinematics analysis of verhead backhand and forehand smash techniques in badminton - Rusdiana, A. (Annals of Applied Sport Science, 2021)
Background. This study aims to analyze the movement of backhand and forehand smash stroke techniques in badminton in three dimensions using a kinematics approach. Objectives. The obtained results were analyzed using a descriptive and quantitative approach. Methods. Furthermore, 24 male badminton players from the university student activity unit with an average age of 19.4 ± 1.6 years, height of 1.73 ± 0.12 m, and weight of 62.8 ± 3.7 kg participated in this study. The study was conducted using 3 Panasonic Handycams, a calibration set, 3D Frame DIAZ IV motion analysis software, and a speed radar gun. Results. The data normalization from the kinematics values of the shoulder, elbow, and wrist joint motion was calculated using the inverse dynamics method. In addition, a one-way ANOVA test was used to identify differences in the kinematics of motion between two different groups. The obtained results showed that the speed of the shuttlecock during the forehand smash was greater than that during the backhand smash. In the maximal shoulder external rotation phase, two variables were identified to have the best results during the forehand smash, i.e., the velocity of shoulder external rotation and wrist palmar flexion. Conclusion. The velocity of shoulder internal rotation, elbow extension, and forearm supination in the maximum angular velocity phase was higher when making a forehand smash.